If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3n + -4) = (7n + 9) + 2 Reorder the terms: 6(-4 + 3n) = (7n + 9) + 2 (-4 * 6 + 3n * 6) = (7n + 9) + 2 (-24 + 18n) = (7n + 9) + 2 Reorder the terms: -24 + 18n = (9 + 7n) + 2 Remove parenthesis around (9 + 7n) -24 + 18n = 9 + 7n + 2 Reorder the terms: -24 + 18n = 9 + 2 + 7n Combine like terms: 9 + 2 = 11 -24 + 18n = 11 + 7n Solving -24 + 18n = 11 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. -24 + 18n + -7n = 11 + 7n + -7n Combine like terms: 18n + -7n = 11n -24 + 11n = 11 + 7n + -7n Combine like terms: 7n + -7n = 0 -24 + 11n = 11 + 0 -24 + 11n = 11 Add '24' to each side of the equation. -24 + 24 + 11n = 11 + 24 Combine like terms: -24 + 24 = 0 0 + 11n = 11 + 24 11n = 11 + 24 Combine like terms: 11 + 24 = 35 11n = 35 Divide each side by '11'. n = 3.181818182 Simplifying n = 3.181818182
| (9x-9)=(4x+16) | | 3x-3x+12=12 | | 13+3=81 | | x+3.5=25 | | (x+3).5=25 | | 26x-4=100 | | 8=-8x+40 | | (3a-4b)-(2a+5b)= | | -10x^2-42x+330=0 | | -7x^2-3x+72=0 | | 3(3k-1)=4(x+3) | | 2(3x+6)+4(x-1)=-32 | | Y-.45=.15 | | 0.5(x-8)=0.2+11 | | 3x+128=90 | | -3+4p+-2p=1 | | 3x+128=52 | | 27-3x=35 | | 3x+128=180 | | 32-5x=x+44 | | 3x-3+2(x-2)= | | 4xy+6x=0 | | 5x+1=6x+5 | | 2(x-3)-7=6-5(x+1) | | x^2-6x+y^2+2y+44=y | | 4a+8=5a-5 | | 17y-5y^2-12=0 | | 2s+7=4s-15 | | -2a+7=a-87a | | y^2-6*y+7=0 | | 4k^2+18k-18=0 | | y=-0.0741x^2 |